Sliding of coherent twin boundaries. Issue 1 (December 2017) - Wang, Zhang-Jie; Li, Qing-Jie; Li, Yao; Huang, Long-Chao; Lu, Lei; Dao, Ming; Li, Ju; Ma, Evan; Suresh, Subra; Shan, Zhi-Wei
Abstract Coherent twin boundaries (CTBs) are internal interfaces that can play a key role in markedly enhancing the strength of metallic materials while preserving their ductility. They are known to accommodate plastic deformation primarily through their migration, while experimental evidence documenting large-scale sliding of CTBs to facilitate deformation has thus far not been reported. We show here that CTB sliding is possible whenever the loading orientation enables the Schmid factors of leading and trailing partial dislocations to be comparable to each other. This theoretical prediction is confirmed by real-time transmission electron microscope experimental observations during uniaxial deformation of copper pillars with different orientations and is further validated at the atomic scale by recourse to molecular dynamics simulations. Our findings provide mechanistic insights into the evolution of plasticity in heavily twinned face-centered cubic metals, with the potential for optimizing mechanical properties with nanoscale CTBs in material design. Coherent twin boundaries (CTBs) in face-centered cubic metals are usually considered unable to slide at room temperature. Here, the authors use in situ transmission electron microscopy and molecular dynamics to show CTB sliding in copper nanopillars when leading and trailing partial dislocations have similar Schmid factors.